1998
DOI: 10.1111/j.1601-0825.1998.tb00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary factors in oral leukoplakia and submucous fibrosis in a population‐based case control study in Gujarat, India

Abstract: OBJECTIVES: To investigate the relationship of specific nutrients and food items with oral precancerous lesions among tobacco users. DESIGN: A population‐based case‐control study. SETTING: Villages in Palitana taluk of Bhavnagar district, Gujarat, India. SUBJECTS AND METHODS: An interviewer‐administered food frequency questionnaire, developed and validated for this population, was used to estimate nutrient intake in blinded, house‐to‐house interviews. Among 5018 male tobacco users, 318 were diagnosed as cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 46 publications
1
35
0
1
Order By: Relevance
“…Many of the OSF patients present with anemias and nutritional deficiencies (Maher et al 1997;Gupta et al 1998). It is not clear how these conditions are related to OSF, although it seems prudent to consider laboratory testing as a secondary objective measure, particularly if designing a medical intervention involving the use of micronutrients, vitamins, or nutritional supplements.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Many of the OSF patients present with anemias and nutritional deficiencies (Maher et al 1997;Gupta et al 1998). It is not clear how these conditions are related to OSF, although it seems prudent to consider laboratory testing as a secondary objective measure, particularly if designing a medical intervention involving the use of micronutrients, vitamins, or nutritional supplements.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Cohort studies have suggested a protective effect of fruits on bladder cancer (Riboli and Norat, 2003), while a very large cohort study did not find a protective effect of five or more servings of fruits and vegetables on total cancer risk (Hung et al, 2004). Both case-control and cohort studies show that high intake of fruits and vegetables are inversely associated with oral precancer (Gupta et al, 1998;Morse et al, 2000;Maserejian et al, 2006) and cancer (Gridley et al, 1990;Levi et al, 1998;Boeing et al, 2006;Pavia et al, 2006). Fruits show a stronger and more consistent inverse association with oral cancer; for vegetables, the strongest inverse association is seen for tomatoes (De Stefani et al, 2000).…”
Section: Carbohydrate Intakementioning
confidence: 99%
“…Chronic areca nut chewing has been strongly linked to the development of oral submucous fibrosis (OSF) (Murti et al 1995;Warnakulasuriya et al 1997;Gupta et al 1998), a chronic progressive pre-cancerous condition characterised by fibrosis of the mucosal lining of the oral cavity and occasionally the upper digestive tract (Maher et al 1991). The oral fibrosis often progresses into the submucosal regions and the underlying muscle, leading to deposition of dense fibrous bands ) and consequently restricts the opening of the mouth (trismus), a hallmark of the condition.…”
Section: Introductionmentioning
confidence: 99%